Pengaruh Adopsi Digital Banking Terhadap Kinerja Keuangan Bank Umum Syariah Dengan Efektivitas Pengelolaan Risiko Sebagai Variabel Moderas - Haryogi, Jeryan; Bakhri, Syaeful; Sudrajat, Anton; Ghofar Saifudin, Abdul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the effect of digital banking adoption on the financial performance of Islamic commercial banks in Indonesia and to examine the moderating role of risk management effectiveness. The research employs a quantitative approach using secondary data from the financial statements of 12 Islamic commercial banks during 2021–2023, resulting in 36 observations. Data were analyzed using panel data regression, and the Random Effect Model was selected as the most appropriate model based on the Chow, Hausman, and Lagrange Multiplier tests. The results show that digital banking adoption has a positive but insignificant effect on financial performance, indicating that the benefits of digitalization have not been fully realized during the observation period. Risk management effectiveness also shows a negative and insignificant direct effect on financial performance. However, the interaction between digital banking adoption and risk management effectiveness demonstrates a positive and significant influence, suggesting that well-managed risk practices strengthen the impact of digital banking on profitability. These findings emphasize that digitalization alone is insufficient to enhance financial performance without strong and effective risk management systems supporting its implementation.